THEORY DEVELOPMENT OF LINGUOPOETICS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article devoted to the views of domestic and foreign scientists on linguopoetics and on the formation and development of linguopoetics. The language of fiction has been researched and studied in the linguistic, poetic and aesthetic direction, scientific and theoretical views on its specific object and subject of research, categories, principles, methods and methodology of research are presented. Researches of scientists form the theoretical basis of a new method of analyses of literary works, including a comprehensive study of language and image of the text in a literary work.
Keywords: linguistics, linguopoetics, literary work, language units, text, image, idea, linguistic analysis, literary analysis, poetic semantics.